From Fritzl to #metoo Twelve Years of Rape Coverage in the British Press - Tranchese, Alessia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"An important, rigorous and very readable book which will be an essential point of reference for future studies of sexual violence in the news. Tranchese demonstrates which myths about rape have persisted, as well as highlighting how they have adapted to the digital news environment. Her analysis is clear and persuasive and provides activists with new tools and evidence to push for change. This is feminist media studies at its best. I cannot recommend this book highly enough." -Karen Boyle, Author #MeToo, Weinstein and Feminism, University of Strathclyde "This book is essential reading for anyone who really wants to understand how the myths and stereotypes around rape are moulded and sustained by the British media, distracting from the profound structural changes required to dismantle misogyny and deliver real justice for women, too often denied by the courts." -Yvonne Roberts, journalist and campaigner This is the first longitudinal study of the language used by the British press to talk about rape. Through a diachronic analysis informed by corpus linguistics and feminist theory, Tranchese examines how rape discourse has (or has not) changed over the past decade. With its detailed investigation of media representations, the book explores how age-old myths about sexual violence re-emerge in different forms within news narratives. Against the backdrop of twelve years of newspaper coverage of rape, including many high-profile cases, this study also traces the rise of "celebrity culture", the emergence of #metoo, and the development of the backlash against it. The author places these historical events and recent trends within broader debates on feminism and the role played by (social) media in shaping contemporary rape discourse. This book provides a much-needed linguistic analysis which will be of particular interest to scholars and students of feminist studies, language and gender, corpus-assisted discourse studies, and gendered crime. Alessia Tranchese is Senior Lecturer in Communication and Applied Linguistics at the University of Portsmouth, UK. Her research interests include the representation of violence against women in the media, online misogyny, and corpus-assisted critical discourse analysis. .
Part 1: Introduction and context -- Chapter 1: Rape: beyond definitions, misconceptions and myths -- Chapter 2: Incidence of rape in the UK -- Chapter 3: British quality press -- Chapter 4: From Fritzl to Weinstein -- Part 2: Theory and Method -- Chapter 5: Theoretical background -- Chapter 6: Corpus building and analysis -- Part 3: The Discourse of Rape -- Chapter 7: Rape and other crimes -- Chapter 8: Rape and ideology in newspapers -- Chapter 9: Who is the rapist? -- Part 4: From Fritzl to Weinstein: Shifting Discourses -- Chapter 10: Consistencies and inconsistencies -- Chapter 11: Rape trials -- Part 5: Conclusion -- Chapter 12: Reflecting upon methodology -- Chapter 13: Concluding remarks.
Keywords: Linguistics; Communication; Sex; Race; Linguistics; Media and Communication; Gender Studies; Race and Ethnicity Studies